Selective sharing permissioning in IoT environments - Silva, Catarina Alexandra Correia da (2022)
The increasing use of smart devices for monitoring spaces has caused an increase in concerns about the privacy of users of these spaces. Given this problem, the legislation on the right to privacy has been worked to ensure that the existing laws on this subject are sufficiently comprehensive to preserve the privacy of users. In this way, research on this topic evolves in the sense of creating systems that ensure compliance with these laws, that is, increase transparency in the treatment of user data. In the context of this dissertation, a demonstrator-based strategy is presented to provide users control over their stored data during the temporary use of an intelligent environment. In addition, this strategy includes transparency guarantees, highlights the right to forgetting, provides the ability to consent and proof of that consent. A strategy for privacy control in such environments is also mentioned in this paper. This dissertation was developed within the CASSIOPEIA project where the case study focuses on the SmartBnB problem where a user rents a smart home for a limited time. This paper presents the developed system that ensures the user’s privacy and control over their data.